Marketing of Indonesian International Tourism from the Perspective of Collaborative Governance - Nobel Pardamean Marpaung; Eko Prasojo (Eduvest - Journal of Universal Studies, 2024)
Tourism is a series of multi-sector activities and involves various stakeholders. The diversity of stakeholders, shared vision and goals, and bounded resources have led to the need for collaborative governance in Indonesian tourism marketing. This study will analyze the conditions of input, process and output of collaborative governance of Indonesian tourism marketing. Bounded marketing resources of Indonesian tourism marketing is the main trigger for the collaborative governance. The motive and objective of collaborative governance of Indonesian tourism marketing is to synergize resources between the government and various stakeholders to improve Indonesia's tourism marketing program. Based on the research results, it was found that most of the conditions of the key elements of collaboration were progressing quite well, but there were still various conditions that needed to be improved. The output results of collaborative objectives related to efficiency, efficacy and equity have been obtained by collaboration participants. The collaborative governance of Indonesian tourism marketing does not yet have standard implementation procedures as guidelines for the MoTCE marketing team. This study suggests a pre-model (initial model) of Indonesian tourism marketing collaborative governance, for further testing and development, to strengthen Indonesian tourism marketing governance.